Utilization of the PROMETHEE algorithm to determine the suitability of the atmospheric environment in traditional buildings - Ana Distia Diva; Sri Winiarti; Murein Miksa Mardhia (Universitas Ahmad Dahlan, 2023)
The village house is an example of a traditional building. The village house is currently used as a community residence. The life of the village house still protects and maintains ancestral customs, including in the form of house architecture. In the process of building a village house, there is one aspect that is used, such as an appropriate environmental atmosphere. Where the building must maintain the beauty of the environment. The importance of paying attention to the atmospheric environment is because the characteristics of these traditional buildings are not lost, especially in the atmospheric environment as historical evidence. Thus, to develop village house buildings, there is a lack of information related to the traditional buildings themselves, such as the past environmental conditions around traditional buildings, road conditions around buildings, beauty and distance between buildings, and building models around conventional houses, to achieve the goal, documentation of the necessary knowledge related to the atmospheric environment for traditional buildings that still maintains or provides an atmosphere like the old days. The research will be conducted using the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) algorithm. The research method is by conducting a literature study, observation, and documentation. Observations and documentation were carried out to collect data in the form of 300 photos of Kampung Rumah in Borobudur, from the data in the form of 300 photos, 9 (nine) were collected. System testing using System Usability Scale (SUS), Black-box, and Expert Judgment. The result of the research is a system for determining the suitability of the environmental atmosphere for village houses in Borobudur using the PROMETHEE algorithm. This research is expected to help determine the village house environment in Borobudur by displaying the final results in the form of outranking and the system test value of 85%.